Cloning and functional analysis of ZmMADS42 gene in maize - Yang Zhao; Jianyu Lu; Bo Hu; Peng Jiao; Bai Gao; Zhenzhong Jiang; Siyan Liu; Shuyan Guan; Yiyong Ma (GM Crops & Food)
Maize (Zea mays L.) is the most important cereal crop in the world. Flowering period and photoperiod play important roles in the reproductive development of maize. This study, investigated ZmMADS42, a gene that is highly expressed in the shoot apical meristem. Agrobacterium infection was used to successfully obtain overexpressed ZmMADS42 plants. Fluorescence quantitative PCR revealed that the expression of the ZmMADS42 gene in the shoot apical meristem of transgenic plants was 2.8 times higher than that of the wild-type(WT). In addition, the expression of the ZmMADS42 gene in the endosperm was 2.4 times higher than that in the wild-type. The seed width of the T2 generation increased by 5.35%, whereas the seed length decreased by 7.78% compared with that of the wild-type. Dissection of the shoot tips of transgenic and wild-type plants from the 7-leaf stage to the 9-leaf stage revealed that the transgenic plants entered the differentiation stage earlier and exhibited more tassel meristems during their vegetative growth period. The mature transgenic plants were approximately 20 cm shorter in height and had a lower panicle position than the wild-type plants. Comparing the flowering period, the tasseling, powdering, and silking stages of the transgenic plants occurred 10 days earlier than those of the wild-type plants. The results showed that the ZmMADS42 gene played a significant role in regulating the flowering period and plant height of maize.